(untitled) (Journal of Academic Research, 2025)
Background: Retained hardware is usually removed during TKR only if no infection is present. We follow clinical and lab criteria to rule out infection and proceed in one session. Methods: In 39 cases, hardware was removed during primary TKR. Most staplers were taken out through the main incision; blade plates needed separate lateral incisions. One tibial nail was partially removed: one DCS plate through lateral dissection. Results: No infections at 6 months. Dropout rate 5%. Over 10 years, no late complications, skin necrosis, or fractures were noted. No metallosis observed. Conclusion: Simultaneous hardware removal during TKR is safe and effective when infection is excluded, and proper planning is followed.